The Integration of Macro and Microeconomic Relations in Dynamic Policy Models : The Case of Saving and Investment Behavior - Bovenberg, Ary (IMF Working Papers; Working Paper ;, 1990)
This paper examines how two types of fiscal policy models, namely, dynamic macroeconomic models and applied general equilibrium models, have integrated macro- and microeconomic relationships within a framework of intertemporal equilibrium. After emphasizing the potential advantages of integrating macro- and microeconomic relations, the study discusses the limitations of intertemporal equilibrium models--in particular the weaknesses of saving and investment theories incorporated in the models. It concludes that, despite recent important advances, policymakers need to exercise caution when they interpret results derived from these models.